Collapse of a cohesive granular column. (25th March 2023) - Gans, A.; Abramian, A.; Lagrée, P.-Y.; Gong, M.; Sauret, A.; Pouliquen, O.; Nicolas, M.
Abstract: Abstract : The collapse of a quasi-two-dimensional column of cohesive granular media is investigated experimentally and numerically in the framework of a continuum model. The configuration is an initial parallelepiped-shaped granular pile, which is suddenly released by opening a retaining door. The experiments rely on a model material developed by Gans et al. ( Phys. Rev. E, vol. 101, 2020, 032904) made of silica particles coated with polyborosiloxane, for which the adhesive interparticle force can be tuned by controlling the thickness of the coating. Numerically, the collapse is simulated using a simple cohesive rheological model implemented in a two-dimensional Navier–Stokes solver. We investigate the role of cohesion on the stability of the column, the mode of failure, the flow dynamics and the geometry of the final deposit. Our results show that the continuum model captures the main features observed experimentally.